Revealing and Concealing Difference: A Critical Approach to Disclosure and an Intersectional Theory of "Closeting". Issue 1 (15th November 2019) - McDonald, James; Harris, Kate Lockwood; Ramirez, Jessica
Abstract: In this essay, we integrate communication research on difference, intersectionality, queer theory, and stigma to develop a critical approach to disclosure that is attentive to power dynamics. Our critical approach to disclosure centers closeting processes in relation to multiple stigmatized, non-normative, and invisible forms of difference, in addition to sexuality/gender. The theory of closeting that we developed contributes to existing disclosure research by (a) highlighting that intersecting forms of difference impact the implications of revealing and concealing information; (b) showing that normativity heavily influences which information is assumed and, therefore, need not be disclosed; (c) establishing that stigma shapes the positive and negative impacts of revelation and concealment; (d) demonstrating that disclosure can have political purposes; and (e) linking the individual, relational, organizational, political, and cultural implications of disclosure. We conclude by discussing the implications of our theory of closeting for scholars working within multiple subfields of communication studies.